Sosialisasi Edukasi Produk Halal Bagi Siswa SMKN 3 Seluma Bengkulu - Susanti, Neri; Wagini, Wagini; Wijaya, Ermi; Indriasari, Nia; Prasetya, Zelinda (Jurnal Dehasen Mengabdi, 2025)
Indonesia has the largest Muslim population in the world, which significantly influences the culture and consumption patterns of its people, especially regarding the increasing demand for halal products. The development of various industries requires heightened awareness of the halal status of products. Teenagers, as one of the primary targets of new products, must have adequate knowledge to recognize whether the products they intend to purchase are halal. This community service aims to provide knowledge about the importance of recognizing halal products, raise awareness among youth about the necessity of consuming halal products in daily life from an early age, and educate students on the importance of carefully selecting halal products. This is to ensure peace of mind, safety, and health for individuals from an early stage. The community service activities were carried out through socialization and educational methods.The results of this community service indicate an increase in students’ awareness from school age, so that when they are later exposed to environments with various products — both halal and those with unclear halal status — they will have the awareness to choose what is appropriate and inappropriate to consume. In addition, participants gained a deeper understanding of the importance of halal labeling. Consequently, consumer trust and purchasing interest — particularly among students of SMK 3 Seluma, Bengkulu — are expected to increase due to the presence of halal labels.